Influence of porosity on erosion behavior and hydrogen permeability of tungsten films - Glazunov, G.P.; Andreev, A.A.; Baron, D.I.; Bondarenko, M.N.; Causey, R.A.; Hassanein, A.M.; Konotopskiy, A.L.; Neklyudov, I.M.; Tarasov, I.K.; Volkov, E.D. (Физическая инженерия поверхности, 2006)
The erosion characteristics of dense and porous W-films deposited on Pd substrates were measured under impact of mirror Penning discharge nitrogen plasma. It is shown that the erosion rate of high porous tungsten films (up to 45% porosity) is similar to that for dense (1 – 3% porosity) tungsten films. At the same time hydrogen permeation through porous tungsten films essentially higher than for dense W coatings and in some cases it approaches to values as for bare Pd. The activation energies of hydrogen permeability measured for two-layer Pd-W systems with high porosity are higher than for dense W-films on Pd (15.44 kJ/mol and 12.8 kJ/mol, accordingly), but these values much lower than the ones for bulk W under gas-driven permeation experiments. The possible reasons of such erosion and permeation behavior are discussed.